KEHIDUPAN NYAI DAN PERGUNDIKAN DI JAWA BARAT TAHUN 1900-1942 - Elfa Michellia Karima (Universitas Negeri Padang, 2017)
This research discusses on the lives of the people of West Java, especially women who make the practice of concubinage as a livelihood to meet the economic needsof the family. The method used in this research is the historical method with the literature study technique by searching the source of literature. By the highnumber of native women who became Nyai in West Java, the problem of this research is about the lives of native women when became Nyai to Europeanpeople. The urgent needs of economy make the women to earn living by working on the farm or became Nyai to European people. There are two kinds ofconcubinage performed, they are official relationship and unofficial relationship. Concubinage official relationship is a relationship legalized in marriage andlegally registered in the Dutch government. However, if the relationship is unofficial, then the marriage is conducted without lawful ties and the absence oflaw protecting the native women. This has a devastating impact that is the spread of venereal disease among Europeans and Natives.